ИЗМЕНЕНИЕ РЕЛАКСАЦИОННЫХ ПРОЦЕССОВ ЭПИТАКСИАЛЬНЫХ СЛОЕВ КРЕМНИЯ ПОСЛЕ ВОЗДЕЙСТВИЯ АТОМА ЭРБИЯ - Шарибаев, М.Б.; Каландарова, Ш.К. (SCIENCE and SOCIETY, 2025)
The article states that in the results of growing erbium-doped epitaxial silicon layers using two different growth modes: conventional molecular beam epitaxy (MBE) and solid-phase epitaxy (SPE) are presented. It has been shown that an erbium-doped silicon layer, when deposited by SPE on a cold substrate and after annealing, exhibits a more intense photoluminescence band at a wavelength of 1.54µm.
Keywords: epitaxial films; doping; photoluminescence; intensity